Servants' stories : life below stairs in their own words, 1800-1950 - Higgs, Michelle (Pen & Sword History, 2015)
Step into the world of domestic service and discover what life was really like for these unsung heroines (and heroes) of society. Between 1800 and 1950, the role of servants changed dramatically but they remained the people without whom the upper and middle classes could not function. Through oral histories, diaries, newspaper reports and never before seen testimonies, domestic servants tell their stories, warts and all - Downton it isn't! Revenge on a mistress with a box of beetles The despair and loneliness of a 14 year old maid The adventure of moving to London to go into service An escape from an unhappy home lifeFind out about the 'servant problem' and how servants found work; how National Insurance began to improve their lot; the impact WW1 had on domestic service; and what was done to try to make the occupation appealing to a new generation. Praise for Michelle Higgs'A delightful layman's guide for tourists from 2014, where you'll glean plenty of juicy detail to paint a more accurate picture of your ancestors' lives.'Family Tree (for A Visitor's Guide to Victorian England)'An enjoyable and well-written social history, helpfully revealing more about what life would have been like 'below stairs'. Who Do You Think You Are' (for Tracing Your Servant Ancestors)'Daily life is recounted with both historical detail and sympathy, aided by numerous first-person accounts.'Your Family Tree (for Life in the Victorian and Edwardian Workhouse)'A lively text which should do much to open up the world of the Victorian prison to the general reader.'Who Do You Think You Are' (for Prison Life in Victorian England).